2017
DOI: 10.1002/pd.4986
|View full text |Cite
|
Sign up to set email alerts
|

A copy number variation genotyping method for aneuploidy detection in spontaneous abortion specimens

Abstract: High-throughput ligation-dependent probe amplification is a rapid and accurate method for aneuploidy detection. It can be used as a cost-effective screening procedure in clinical spontaneous abortions. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 25 publications
(42 reference statements)
0
34
0
5
Order By: Relevance
“…An abundance of reports into human miscarriages cite aneuploidy as the greatest cause of the pregnancy failure 17,39 . In contrast, reports of aneuploidy associated with pregnancy loss in domesticated animals is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…An abundance of reports into human miscarriages cite aneuploidy as the greatest cause of the pregnancy failure 17,39 . In contrast, reports of aneuploidy associated with pregnancy loss in domesticated animals is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…An abundance of reports into human miscarriages, cite aneuploidy as the greatest cause of the pregnancy failure [20, 21]. In contrast, reports of aneuploidy associated with pregnancy loss in domesticated animals is rarely reported, and never in the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Aneuploidy (gain or loss of a whole chromosome) is well documented in human spontaneous abortion [20, 21] and is associated with advancing maternal age. Some human autosomal trisomies (13, 18, and 21) have been identified in infants following live births, although these usually present with significant developmental pathologies [22] with only trisomy 21 individuals surviving to adulthood [23], and no documented surviving monosomies.…”
Section: Introductionmentioning
confidence: 99%
“…Then, universal primers labeled with uorescent markers were used to amplify the concatenate products by PCR. After ampli cation, the PCR products were separated and detected by uorescence capillary electrophoresis, then the copy number of target regions were calculated by analyzing the peak height of electrophoretogram, the detailed work ow refer to the study Chen, S et al reported 14 . There were totally 170 (for Chr1-12 and Chr16-17, there 8 probes for each chromosome; for Chr13-15, Chr21-22 and ChrY, there 5 probes for each chromosome; for Chr18-Chr20 and ChrX, there 7 probes for each chromosome) pairs of probes targeting 24 chromosomes were designed for the aneuploidy detection.…”
Section: Aneuploidy Detection By Hlpamentioning
confidence: 99%